1962
DOI: 10.1177/002383096200500401
|View full text |Cite
|
Sign up to set email alerts
|

The Identification and Discrimination of Synthetic Vowels

Abstract: A series of thirteen two-formant vowels was synthesized and used as the basis of labelling and discrimination tests with a group of English-speaking listeners. The sounds varied only in F1/F2 plot and the resulting vowel qualities were such that listeners found no difficulty in assigning each sound to one of three phonemic categories, those of the vowels in bid, bed and bad. The results of the tests were compared with those previously obtained in experiments involving the consonant phonemes /b, d, g/. It appe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
177
2

Year Published

1997
1997
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 278 publications
(185 citation statements)
references
References 9 publications
6
177
2
Order By: Relevance
“…For example, neither affricates or fricatives (Ferrero, Pelamatti, & Vagges, 1982;Rosen & Howell, 1987) nor vowels (Abramson, 1961;Fry, Abramson, Eimas, & Liberman, 1962) are categorically perceived. Might we expect this to be true of signs as well?…”
Section: Discussionmentioning
confidence: 99%
“…For example, neither affricates or fricatives (Ferrero, Pelamatti, & Vagges, 1982;Rosen & Howell, 1987) nor vowels (Abramson, 1961;Fry, Abramson, Eimas, & Liberman, 1962) are categorically perceived. Might we expect this to be true of signs as well?…”
Section: Discussionmentioning
confidence: 99%
“…Unlike consonants, vowel discriminability cannot be closely predicted from the identification data, which itself is much more prone to context effects (Eimas, 1963). Relatively continuous perception has been found repeatedly in the /i/-/I/-/E/ continuum (Fry et al, 1962;Stevens et al, 1963;Stevens et al, 1964), as well as in perception of vowel duration (Bastian and Abramson, 1962) and perception of tones in Thai (Abramson, 1961). Further support for more continuous perception of vowels comes from mimicry experiments (Chistovich, 1960;Kozhevnikov & Chistovich, 1965): When participants were asked to mimic stop consonants and vowels, their ability to reproduce vowels accurately was much greater than for consonants, which tended to be reproduced with prototypical members of the category.…”
Section: Vowel Effectsmentioning
confidence: 99%
“…Discrimination is little better than would be expected if listeners used only category labels to distinguish sounds, and between-category differences are extremely pronounced (Liberman et al, 1957;Wood, 1976). At the other end of the spectrum, vowel discrimination is much more continuous, so much so that some early experiments seemed to suggest that vowels displayed no categorical effects at all (Fry et al, 1962). Since these classic studies, it has become evident that stop consonant perception is not purely categorical, while vowel perception can also exhibit categorical effects (Pisoni & Lazarus, 1974;Pisoni, 1975).…”
Section: Introductionmentioning
confidence: 98%
“…Yet, according to (Repp, 1984p. 260): "In the earliest discrimination study, (Fry et al, 1962) found no discrimination peak at category boundary, but this was probably due to a ceiling effect, coupled with the use of imperfectly controlled stimuli. Most later studies (e.g., Fujisaki and Kawashima, 1969;Fujisaki and Kawashima, 1970;Pisoni, 1971;Stevens et al, 1969) have found clear peaks on vowel continua, so there is good reason to believe that there is a phonetic component in vowel discrimination".…”
Section: Experiments 2: Ax Discrimination Experimentsmentioning
confidence: 99%